Influence of Implant-Abutment Contact Surfaces and Prosthetic Screw Tightening on the Stress Concentration, Fatigue Life and Microgap Formation: A Finite Element Analysis - João Paulo Mendes Tribst; Amanda Maria de Oliveira Dal Piva; Laís Regiane da Silva-Concílio; Pietro Ausiello; Les Kalman (MDPI AG, 2021)
The purpose of this in silico study was to investigate the effect of abutment screw torque and implant-abutment contact surfaces on the stress generation, microgap formation and simulated fatigue life of an external hexagon connection under oblique loading. Three-dimensional numerical models of the external hexagon implant were modeled containing two different implant-abutment contact surfaces (with and without contacting the hexagon axial walls) as well as using screw torques of 20 Ncm or 30 Ncm. Following the ISO 14801, an oblique load of 100 N was applied to the prosthesis. The von Mises stress, microgap formation, safety factor and fatigue life were obtained. The stresses in the abutment screw and implant were minimally influenced by the screw torque. However, this minimal stress in the screw with a 30 Ncm torque reduced the calculated fatigue life in comparison with 20 Ncm when the external hexagon axial walls were not in contact at the implant-abutment interface. The safety factor for the implant was higher when using minimal surfaces at the abutment-interfaces; however, it compromised the screw safety factor increasing its failure probability. The higher the screw torque, the lower was the microgap formation at the implant-abutment interface. However, the calculated residual stress is proportional to the applied torque, reducing the fatigue life in the screw. This effect can be attenuated using an implant-abutment system with more contacting surfaces.